Temporal Expression Dynamics of Plant Biomass-Degrading Enzymes by a Synthetic Bacterial Consortium Growing on Sugarcane Bagasse - Jiménez, Diego Javier; Chaib De Mares, Maryam; Salles, Joana Falcão (Frontiers in Microbiology, 2018)
Plant biomass (PB) is an important source of sugars useful for biofuel production, whose degradation efficiency depends on synergistic and dynamic interactions of different enzymes. Here, using a metatranscriptomics-based approach, we explored the expression of PB-degrading enzymes in a five-species synthetic bacterial consortium during cultivation on sugarcane bagasse as a unique carbon source. By analyzing the temporal expression dynamics of a selection of enzymes we revealed the functional role of each consortium member and disentangled the potential interactions between them. Based on normalized expression values and the taxonomic affiliation of all the transcripts within thirty carbohydrate-active enzyme (CAZy) families, we observed a successional profile. For instance, endo-glucanases/-xylanases (e.g. GH8, GH10 and GH16) were significantly expressed at 12 hours, whereas exo-glucanases (e.g. GH6 and GH48) and alpha-arabinosidases/beta-xylosidases (e.g. GH43) were highly expressed at 48 hours. Indeed, a significant peak of extracellular β-xylosidase activity was observed at this stage. Moreover, we observed a higher expression of several CAZy families at 12-48 hours, suggesting easy access to the main plant polysaccharides. Based on this evidence, we predicted that the highest level of collaboration between strains take place at the initial stages of growth. Here, Paenibacillus, Brevundimonas and Chryseobacterium were the most important contributors, whereas Stenotrophomonas was highly active at the end of the culture (96-192 hours) without contributing to a large extent to the expression of lignocellulolytic enzymes. Our results contribute to the understanding of enzymatic and ecological mechanisms within PB-degrading microbial consortia, yielding new perspectives to improve PB saccharification processes.